Numerical Investigation of Gas Mixture Length of Nitrogen Replacement in Large-Diameter Natural Gas Pipeline without Isolator - Hongjun Zhu; Qinghua Han (Journal of Applied Mathematics)
Nitrogen replacement is a key process for natural gas pipeline before it is put into operation. A computational fluid dynamic model coupled to a species-transportation model has been used to investigate the gas mixture length of nitrogen replacement in large-diameter pipeline without isolator. A series of numerical simulations are performed over a range of conditions, including pipe length and diameter, inlet rate, and inclination angle of pipe. These affecting factors are analyzed in detail in terms of volume fraction of nitrogen, the maximum gas mixture length, and gas mixture length varied with time. Gas mixture length increases over time, and the maximum gas mixture length is present at outlet of pipe. Long and large-diameter pipe and fast speed of nitrogen lead to long length of mixed gas, while large inclination angle of pipe brings about short length. Several fitting formulas have been obtained, which can predict the maximum gas mixture length in gas pipelines. The used method of fitting formula is shown in the paper by examples. The results provide effective guidance for practical operation of nitrogen replacement.